EVALUATION OF MARGINAL ADAPTATION AND MICROLEAKAGE OF DIFFERANT ALL-CERAMIC PORCELAIN SYSTEMS - Suat Yaluğ; Akın Coşkun (Cumhuriyet Dental Journal, 2022)
ABSTRACT Purpose: This study evaluated the marginal adaptation and microleakage of the İn-Ceram Alumina, In-Ceram Zirconia and Finesse press all-ceramic porcelain systems. Material and methods: Thirty maxillary Central teeth extracted for periodontal reasons without caries and cracks were divided equally into three group and there was no control group; only the three systems were compared. Sample teeth cemented were stored in distile water for 24 hours. Then, they were applied to a repeated thermal cycle for 500 times. The samples were left in %5 of basic fuchsin dye for 24 hours. For the marginal adaptation rankings, all of the sample teeth for which cross-sections were made were moved into the metal microscope (Scherr Turico St. James/ Minn./ USA) and the marginal adaptation degrees were measured in both the palatinal and vestibul regions by measuring twice with x10 enlargement at micron level. For the statistical evaluations of marginal adaptation and microleakage values, Kruskal Wallis test has been used (p>0.05). Results: The differences between the three all-ceramic porcelain systems are not significant (p>0.05), α=0.05). Conclusion: The Finesse porcelain system caused the least leakage in both regions. In second place in both regions was In-Ceram Alumina, In-Ceram Zirconia caused the most leakage in both regions. The biggest margin gap in the palatal region was seen in the Finesse porcelain system, In-Ceram Zirconia in second place. The least marginal gap was caused by the In- Ceram Alumina porcelain system.